Research on Ground Tie-down Characteristics of Typical-layout Civil Aircraft - BAI Feng; WANG Qizhi (Hangkong gongcheng jinzhan, 2022)
The aircraft is impacted by severe weather on parking apron,and the aerodynamic research of parking is important for parking safety.In order to analyze the aerodynamic difference of typical-layout civil aircraft induced by ground cross-wind,and determine the typical tie-down loads,the scale mode and fixed ground plate in wind tunnel are used to simulate the aircraft park aiming at two typical-layout civil aircraft,the aerodynamic forces of aircraft which induced by cross-wind with the angles from 0° to 180° are measured.The disassemble test method is adopted to analyze the empennage aerodynamic coupling.The reasons of large pitching moment of high horizontal tail layout and small pitching moment of low horizontal tail layout at cross-wind research are confirmed in the condition of the empennage aerodynamic coupling.The engineering estimation method is used to obtain the nose landing gear tie-down loads at rear tipping condition.The results show that the deference of aerodynamic characteristics can increase the nose landing gear tie-down loads of low horizontal tail aircraft,and is of less influence on high horizontal tail aircraft.